Traditional and New Methods of Bone Age Assessment-An Overview - Monika Prokop-Piotrkowska; Kamila Marszałek-Dziuba; Elżbieta Moszczyńska; Mieczysław Szalecki; Elżbieta Jurkiewicz (Galenos Yayincilik, 2021)
Bone age is one of biological indicators of maturity used in clinical practice and it is a very important parameter of a child's assessment, especially in paediatric endocrinology. The most widely used method of bone age assessment is by performing a hand and wrist radiograph and its analysis with Greulich-Pyle or Tanner-Whitehouse atlases, although it has been about 60 years since they were published. Due to the progress in the area of Computer-Aided Diagnosis and application of artificial intelligence in medicine, lately, numerous programs for automatic bone age assessment have been created. Most of them have been verified in clinical studies in comparison to traditional methods, showing good precision while eliminating inter- and intra-rater variability and significantly reducing the time of assessment. Additionally, there are available methods for assessment of bone age which avoid X-ray exposure, using modalities such as ultrasound or magnetic resonance imaging.